Undiagnosed hypertension in Peru: analysis of associated factors and socioeconomic inequalities, 2019 - Guerrero Díaz, Delia Vanessa (2021)
Objective: To determine the factors associated and measure the socioeconomic inequalities in people with undiagnosed hypertension in Peru. Materials and methods: An observational, cross-sectional, analytical study was performed using data from the 2019 Demographic and Family Health Survey (ENDES, acronym in Spanish) database. The dependent variable was the presence of undiagnosed hypertension (mean systolic blood pressure ≥140 mmHg and/or mean diastolic blood pressure ≥90 mmHg in the two blood pressure measurements and with no prior diagnosis of hypertension by a health care professional). Adjusted prevalence ratios were estimated to determine the factors associated with undiagnosed hypertension. The socioeconomic inequality in undiagnosed hypertension was estimated using concentration curves and the Erreygers concentration index. Results: 67.2% of 3697 persons with hypertension had not been diagnosed. Non-diagnosis of hypertension was more prevalent in men who were residents of the Coast and in inhabitants residing at more than 3000 m above sea level. Being 50 years of age or older, having health insurance, being obese and having diabetes mellitus were associated with a lower prevalence of undiagnosed hypertension. Inequality of the non-diagnosis of hypertension was found to be concentrated in the poorest population. Conclusions: At least one out of every two adult Peruvians with hypertension have not been diagnosed with this condition. Socioeconomic inequality was found, as well as socio-demographic and health-related factors associated with undiagnosed hypertension. Our findings identify some population subgroups in which interventions for screening and treatment of hypertension should be prioritized in order to reduce both inequalities and complications of hypertension among the most vulnerable.